Microbiota and sensorial attributes of buffalo meat stored under vacuum packaging: combined impact of marination, citrox and oregano essential oil - Tareq Osaili (11550286) (2023)
The demand for marinated meat and natural antimicrobials has increased in the last decade. This study aimed to examine the antimicrobial and sensorial effects of natural citrox (0.2% v/w) and oregano essential oil (0.1% v/w) or their combination on marinated buffalo meat stored under vacuum at two storage conditions of 4°C and 12°C. In the control (without marinade), the population of all the spoilage microorganisms increased by 3.8–6.3 and 4.5–6.3 log cfu/g, at 4 and 12°C, respectively, during storage. On the last day of storage, at both 4 and 12°C, the spoilage microorganisms’ populations were lower for the marinated meat (without citrox and EO) by 1–2 log cfu/g (based on microorganism type) compared to its unmarinated counterpart. The combination of citrox and oregano essential oil (EO) resulted in decreases of 3.0–6.8 and 3.2–6.8 log cfu/g for mesophilic aerobic bacteria, Pseudomonas spp. lactic acid bacteria (LAB), Brochothrix thermosphacta, Enterobacteriaceae, and yeasts, at 4 and 12°C, respectively. The pH values of the treatments with citrox and oregano EO followed a steadily decreasing (P < .05) trend during storage. The recorded sensory data supported that meat marinated with those 2 natural antimicrobials led to a buffalo meat of acceptable quality. Marinade combined with citrox and oregano EO can provide a potential not previously studied solution for buffalo meat preservation. Other Information Published in: International Journal of Food Properties License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10942912.2023.2238919